“What do employers want?” A study of online job advertisements for translators in Thailand - Poonlarp, Tongtip; Leenakitti, Nattharath (Journal of Language and Culture, 2016)
This research involves an investigation into the needs and expectations that employers have towards translators in Thailand. The aim of this study was to identify preferred qualifications of translator recruits from the perspectives of employers in the hope of adjusting training to the realities of the labor market. To this end, 95 job advertisements for translators posted in eight online recruitment websites were collected between 31 January 2012 and 21 February 2012, their content thenanalyzed and codified using Microsoft Excel and SPSS. The areas investigated included general information about the job (job titles and responsibilities, types of businesses, salary), required qualifications (sex, age, education, experience, knowledge, skills and aptitude), languagesinvolved, as well asother related information (salary). In addition to providing valuable insights into the employers’ needs and expectations on the one hand, the advertisements reflected some general misconceptions about the translation profession on the other, including the ‘anyone who knows the language can translate’ and ‘the translator is an interpreter’ notions, as well as the mismatch between the job titles advertised and the described responsibilities. Based on the findings, the authors suggest how both language and translation degree programs can prepare their graduates for future translation careers.